Administration of a Student Athlete Survey & Implications for the Quality of Advising & Related Services - Nelson, Eileen S.; Boyajy, Jennifer L. (My University, 2000)
This paper describes the results of an exit survey administered to student-athletes at a southeastern Division I university. Graduating student-athletes were asked to complete a survey that was created in an effort to determine their level of satisfaction with the OADSA, their coaches, their major department advisors, and special campus services. This student-athlete survey is in addition to the NCAA mandated exit survey given to graduating student-athletes. The questionnaire involved 74 items with a Likert-type scale for responses ranging from Strongly Agree to Strongly Disagree to Not Applicable. Of the 66% of graduating student-athletes (n=45) who participated,15 of 25 Varsity Athletic teams were represented. The information obtained from the exploratory survey was used by the Athletic Department as a guide for the implementation of the CHAMPS/Life Skills Program. Implications of the exit survey were discussed. The results indicated that the student-athletes were slightly more satisfied with their athletic advisors than with their major advisors. Of the four special campus services addressed by the survey: the Office of Career Services, the Center for Multicultural Services. the Counseling and Student Development Center, and the Reading and Writing lab, the greatest amount of students reported visiting the Office of Career Services (21). In addition, student-athletes reported being the most satisfied with the quality of their experience at the Reading and Writing labs. No significant differences were found in the level of satisfaction in any of the assessed areas.
Keywords: seniors; transitions; academic support; student development satisfaction